Environmental Toxicity and Its Ayurvedic Management Through Agada Tantra: A Comprehensive Review - Kumar, Pawan; Namewar, Prasad (Journal of Neonatal Surgery, 2025)
Environmental toxicity has become an alarming public health issue due to increased industrialization, urbanization, and widespread use of synthetic chemicals. Exposure to heavy metals, pesticides, air pollutants, and industrial effluents contributes significantly to chronic illnesses including respiratory diseases, neurological disorders, hormonal imbalances, immune suppression, and even cancer. While modern medicine offers treatments like chelation therapy, it often addresses only the symptomatic aspect, lacking a holistic approach.Ayurveda, the ancient Indian system of medicine, offers a unique perspective on toxicity through its specialized branch called Agada Tantra, dedicated to the study and management of poisons (Visha). Classical Ayurvedic texts describe various forms of toxins such as Dushi Visha (latent toxins), Garavisha (artificially compounded toxins), and Jangama-Sthavara Visha (animal and plant-based toxins), which can be correlated with modern environmental pollutants.Agada Tantra emphasizes preventive and curative measures, using therapies like Vamana (emesis), Virechana (purgation), Nasya (nasal therapy), and administration of Vishaghna Dravyas (antidotal herbs) such as Guduchi, Haridra, and Shankhpushpi. These treatments aim not only to expel accumulated toxins but also to restore balance and enhance the body’s resilience through Rasayana (rejuvenation) therapies.This review highlights the relevance of Agada Tantra in addressing contemporary environmental toxicity. By integrating Ayurvedic principles with modern toxicology, it offers a comprehensive, preventive, and sustainable model for managing toxin-induced diseases. This holistic approach makes Agada Tantra a promising tool in current environmental health management.